Willingness to vaccinate and willingness to pay for vaccination against peste des petits ruminants in Linguère, Senegal - Ilboudo, Guy S.; Wanyoike, Francis N.; Moore, V.B.; Rich, Karl M.; Djigo, C.A.T.; Dione, Michel M. (International Livestock Research Institute, 2022)
Objective As part of the national strategy for controlling and eradicating peste des petits ruminants (PPR), Senegal organizes an annual mass vaccination campaign. The government subsidizes the vaccine by XOF 69 ($0.1), while the farmers pay only XOF 50 ($0.08), making a total cost of vaccine of XOF 119 ($0.18). This study aims to identify the factors that influence the decision of farmers to vaccinate their animals against PPR and their willingness to pay for improved vaccination service. Methods Using a choice experiment with 200 farmers in four communes of the department of Linguère, we considered a combination of attributes that improved the vaccine quality and delivery. These include, location of vaccination activities (home vs parc), vaccination strategy (individual vs group), type of vaccine (thermotolerant vs thermolabile), combination of vaccine with other services (other small ruminant vaccines vs deworming), nature of vaccination (elective vs compulsory), different costs of the vaccine. Results Preliminary descriptive results are reported here. Most of the respondents are male (84%) and have no formal education level (62%). Livestock is the main source of income for 85% of the respondent’s households. Most of the farmers keep more sheep than goat (77%) and the flock size is ranged from 3 to 700 animals with a median value of 70 animals. The median reported morbidity and mortality rates are respectively 20% and 10%. Nearly 40% of farmers said they have never vaccinated their animals against PPR. The reasons for non-vaccination were that they have never heard of PPR vaccination (51%), the non-availability of the vaccine (29%) and cultural barriers (10%). Most farmers preferred an annual vaccination (64%) and home vaccination (91%) to save travel time. Farmers state that they would vaccinate more if vaccination is combined with other services such as deworming (99%) or with another small ruminant vaccine (97%). The main expectations of the farmers in term of improved vaccine are the reduction in mortality (98%), increase in productivity (99%) and the increase in the market price (83%). The main factors influencing the decision of farmers to vaccinate are respectively the benefit of the vaccine (98%), the type of vaccinator (91%), the access to the information (86%), the vaccine availability (80%), the vaccination certificate (76%) and other reasons such as vaccination period (41%), immunity duration of the vaccine (31%), vaccination cost (30%), vaccination strategy (27%) and type of identification of vaccinated animals (26%). Conclusion Choice experiment analysis are ongoing. Results from this study will be useful in informing the implementation of vaccination campaigns against PPR in Senegal, and in the Sahel in general given that the production systems are similar.